PERSEPSI SISWA TERHADAP PEMBELAJARAN PERMAINAN TRADISIONAL BOI-BOAN KELAS 6 SEBAGAI MEDIA PENGUATAN NILAI KEBANGSAAN DI PELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN - Pujiyanti, Ina; Andaryani, Eka Titi; Avrilianda, Decky; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to synthesize the literature on students’ perceptions of the traditional game boi-boan or boy-boyan as a medium for reinforcing national values in Physical Education, Sports, and Health (PJOK) instruction in elementary schools. The study employed a Systematic Literature Review (SLR) design following the PRISMA 2020 guidelines. The literature search was conducted via Google Scholar, Garuda/OJS journal portal, Semantic Scholar, and manual tracking of reference lists using keywords related to traditional games, PJOK, elementary schools, character education, national values, and student perceptions. The publication range was limited to 2021–2026. Of the 186 initial articles identified, 20 publications met the inclusion criteria and were analyzed thematically. The study’s findings indicate that traditional games in Physical Education and Health (PJOK) foster active participation, motor skill development, cooperation, sportsmanship, discipline, responsibility, cultural identity, and positive student perceptions. Boi-boan is particularly relevant as it integrates teamwork, courage, strategy, adherence to rules, and fair play. However, reinforcing these values is not sufficient through the mere implementation of the game; teachers need to engage in explicit reflection so that students understand the national significance behind the play activity. Therefore, boi-boan needs to be designed as structured Physical Education and Health (PJOK) learning through cultural introduction, safe game modifications, group participation, reflective dialogue, and behavior-based character assessment.